Aquacultural facilities and equipment - Mal, Bimal Chandra (Academic Press, 2021)
Aquaculture Facilities and Equipment is a practical resource on the technical aspects needed for experts in the field to understand a high-performance aquaculture facility, its design and form, and the materials and systems used within the facility. The book is written at a level suitable for both field experts and students alike. It includes topics such as pond construction machinery, pumps for aquaculture, aeration for aquaculture, fish feeders, filtration systems in aquaculture, hatchery, raceways and tanks, and cage and pen culture. This book is based on 30 years of research that is presented as a useful reference to enhance efficient aquaculture production. It will be very helpful for experts working in related fields of fishery development and for those teaching fishery science and engineering courses.